Enhanced Audio Steganografi dengan Algoritma Advanced Encryption Standard untuk Pengamanan Data pada File Audio - Peling, Ida Bagus Adisimakrisna; Sastra, Nyoman Putra (Jurnal Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2018)
Ease of accessing and delivering information makes the Internet more and more needed. But the ease also provides greater opportunities for leaking of information that is confidential. To handle the security of information exchange that is confidential then developed the method of data security on audio using AES (Advanced Encryption Standard) and EAS (Enhanced Audio Steganography) algorithm. From the research results can be concluded by using AES method as cryptography and EAS as steganography, audio file quality can be said good because of the overall test scenario conducted the lowest SNR value obtained is 49.33dB while the highest SNR value is 51.10dB.